Characteristics of dust mite sublingual immunotherapy-associated adverse events in the early phase - Chen, Ming; Lin, Lin; Yan, Maoxiao; Xu, Chong; Chai, Ruonan (Frontiers in Medicine, 2022)
Background: Few studies reported the characteristics of house dust mite (HDM) sublingual immunotherapy (SLIT) adverse events (AEs) during early phase treatment. The aim of this prospective study was mainly to explore the characteristics of AEs in allergic rhinitis (AR) patients during 6 months of HDM SLIT. Methods: A total of 242 patients with AR were enrolled in this study. Telephone follow-up and administration were conducted in the every week of the first month, the third month, and the sixth month of SLIT treatment. Furthermore, the early efficacy, AEs, and compliance were analyzed in our study. Results: Overall, 70.25% (170/242) of the AR patients completed the study, while 29.75% (72/242) of the AR patients failed to complete the whole 6 months of SLIT treatment process. On the whole, symptoms improved in 87.65% (149/170) of patients including 34.12% (58/170) well-controlled and 53.53% (91/170) partially controlled. The correlation analysis results showed that the treatment effect was negatively correlated with the age (r=-0.1614, P=0.0355). The AEs mainly occurred in the first month, comprised of local rashes, gastrointestinal reactions, and itching of mouth and tongue. Subgroup analysis in the first month showed the itching of mouth and tongue, gastrointestinal reactions, fatigue, and other AEs in ≥14 years old group (14-65 years old, n=42) were significant differences when compared with that in the <14 years old group (4-13 years old, n=128, all P <0.05). In the study, the main reasons for terminated immunotherapy were drug inaccessibility, loss of follow-up and long course of treatment. Conclusion: Patients with AR who received HDM SLIT revealed an early efficacy after 6 months, with AEs mostly occurred in the first month.